Evolution of free, complexed, and total serum prostate-specific antigen and their ratios during 1 year of follow-up of men with febrile urinary tract infection. - Zackrisson, B; Ulleryd, P; Aus, G; Lilja, H; Sandberg, T; Hugosson, J (2003)
OBJECTIVES: To determine the serum values of free, complexed, and total prostate-specific antigen (PSA) and their ratios in men with febrile urinary tract infection (UTI) during 1 year of follow-up. METHODS: A total of 54 men were prospectively enrolled in the study, and serum samples were obtained at the acute stage of the UTI and after 1, 3, 6, and 12 months. RESULTS: Most men had a rise (median 3.1, 7.2, and 14.1 ng/mL, respectively) in free PSA (fPSA), complexed PSA (cPSA), and total PSA (tPSA) during the acute phase of the UTI. After 1 month, fPSA rapidly decreased to levels that were maintained during the rest of the follow-up period, and cPSA and tPSA declined more slowly. At 1, 3, and 6 months after the infection the fPSA/tPSA and fPSA/cPSA ratios were abnormal in one half to two thirds of the men (median ratio 11%, 15%, and 16% and 17%, 24%, and 24%, respectively), comparable to findings in patients with prostate cancer. CONCLUSIONS: These results confirmed that the prostate is involved in men with febrile UTI. The low fPSA/tPSA and fPSA/cPSA ratios in combination with sustained elevations of cPSA and tPSA for up to 6 months after UTI could be falsely interpreted as a sign of prostate cancer. The prolonged elevation of cPSA indicates a long-lasting inflammation of the nonadenomatous parts of the prostate.